Health of the person in modern conditions and Orthodox psychotherapy - Eugeniya Kocherga (Волинський благовісник, 2017)
In the article an attempt to analyze the relationship between human passions with negative emotional states as causes of disease was implemented. The possibilities of Orthodox psychotherapy in the treatment of diseases are also revealed.